A Phenomenological Study of Exclusive Breastfeeding Practices among the Banjar Ethnic Community in the Working Area of Karang Intan 1 Community Health Center - Anila Iliani; Herawati Herawati; Hardyan Sauqi; Adi Nugroho; Nelly Al Audhah (PSPP JOURNALS, 2026)
Exclusive breastfeeding coverage in Indonesia remains below the national target of 80%. In the service area of Karang Intan 1 Community Health Center, the coverage was only 17.3%, contributing to the high prevalence of stunting. This study aimed to explore the experiences of exclusive breastfeeding among the Banjar tribe from socio-ecological and cultural perspectives. A qualitative study with a phenomenological design was conducted involving 27 participants, including breastfeeding mothers, husbands, family members, traditional and religious leaders, and health workers. Data were collected through in-depth interviews and analyzed thematically using Bronfenbrenner’s Social Ecology Theory and Leininger’s Sunrise Model. The findings showed that exclusive breastfeeding practices are influenced by interactions among family, community, and cultural environments. Support from husbands and parents was essential but often conflicted with traditional practices, such as pre-lactation feeding and postpartum dietary restrictions. Community health cadres and local leaders strengthened social support, while adapting the local Bedadah tradition promoted acceptance of breastfeeding messages. However, formula milk promotion remained a major barrier. The study concludes that exclusive breastfeeding among the Banjar tribe is shaped by the interaction of cultural beliefs, family support, and community influences. Improving breastfeeding outcomes requires culturally sensitive health education, active involvement of family and community leaders, and reinforcement of local cultural values that encourage exclusive breastfeeding.